2019
DOI: 10.1155/2019/1279318
|View full text |Cite
|
Sign up to set email alerts
|

Impact of HIV-1 Infection and Antiretroviral Therapy on Bone Homeostasis and Mineral Density in Vertically Infected Patients

Abstract: Daily assumption of antiretroviral drugs and HIV-related immune activation lead to important side effects, which are particularly evident in vertically infected patients. Bone homeostasis impairment and reduction of bone mineral density (BMD) is one of the most important side effects. Primary aim of this study is to assess the prevalence of bone homeostasis alterations in a group of vertically infected patients; secondary aim is to analyze the relationship between bone homeostasis alterations and anthropometri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…PI was used with most participants, which limited the analysis of its effect on BM. BMD showed a negative correlation with age, as observed recently 20,22 . Pubertal delay and disease chronicity justify this association.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…PI was used with most participants, which limited the analysis of its effect on BM. BMD showed a negative correlation with age, as observed recently 20,22 . Pubertal delay and disease chronicity justify this association.…”
Section: Discussionsupporting
confidence: 83%
“…This variability is related to the profiles involved, especially age and clinical category. Studies with older participants 2,22 or those with a predominance of category C 2,9 showed higher rates of impaired BM. When greater age and a predominance of category C are associated, the occurrence of low BM reaches 32% 2 .…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…While antiretroviral therapy (ART) has revolutionized human immunodeficiency virus type one (HIV-1) infection, treatment and preventative drug regimens require strict adherence to daily dosing. With substantive extensions in longevity and quality of life, ART still remains associated with a number of adverse drug reactions, poor regimen compliance and drug resistance (1)(2)(3). Comorbid events include stigma of infection, depression and neuropsychiatric disorders associated with or without substance abuse.…”
Section: Introductionmentioning
confidence: 99%